Proposed guidelines for appropriate utilization of superficial radiation therapy in management of skin cancers. Zemtsov‐Cognetta criteria. Issue 4 (30th March 2023) - Zemtsov, Alexander; Cognetta, Armand; Marvel, John; Logan, Ann
Abstract: Objective: To develop appropriate use criteria (AUC) for the treatment of basal cell and squamous cell carcinoma by superficial radiation therapy (SRT) technique. Material and Methods: Delphi‐type discussion of the experts. Results: Presented in Figure 1. Conclusion: These AUCs are in compliance both with the position statement of the American Academy of Dermatology (AAD) and the ASTRO Clinical Practice Guideline on this subject. It is further recommended that SRT will be only performed by either a dermatologist who is board certified in Mohs surgery (MDS) and who had adequate SRT training or by radiation oncologists. Hopefully, this publication will stimulate further discussion on this topic.